Ossifying fibromyxoid tumor in an elderly patient: A case report and literature review. Issue 4 (July 2021) - Morita, Yoshihiro; Iwagami, Takaki; Niki-Yonekawa, Atsuko; Yano, Hiroyuki; Kusuyama, Yukiko; Morita, Nobuo; Uzawa, Narikazu
Abstract: An ossifying fibromyxoid tumor (OFMT) is a rare mesenchymal neoplasm of borderline malignant potential that usually arises in the subcutaneous tissue of the extremities, trunk, and head and neck area; it is extremely rare in the oral cavity. OFMTs occur in adults, mostly middle-aged, and are slightly more common in men, with a median age of approximately 50 years. A case of an OFMT of the gingiva in the maxillary molar area in an elderly patient is presented. An 88-year-old woman presented to our department with a painless swelling of the gingiva in the right maxillary molar area. Radiography showed a lesion with absorption of the right maxillary alveolar bone. The lesion was removed from the maxillary gingiva under general anesthesia. The histopathological diagnosis was OFMT. A patient with OFMT needs long-term postoperative follow-up because it has a recurrence rate of about 30 %.